2015
DOI: 10.1021/acs.macromol.5b00079
|View full text |Cite
|
Sign up to set email alerts
|

Chain Trajectory and Crystallization Mechanism of a Semicrystalline Polymer in Melt- and Solution-Grown Crystals As Studied Using 13C–13C Double-Quantum NMR

Abstract: The re-entrance sites, successive chain-folding number ⟨n⟩, and chain-folding fraction ⟨F⟩ of the chain-folding (CF) structure of 13C CH3-labeled isotactic poly­(1-butene) (iPB1) with an weight-averaged molecular weight (⟨M w⟩ = 37 K g/mol) in solution- and melt-grown crystals as a function of crystallization temperature (T c) were determined using solid-state (SS) NMR. The solution- and melt-grown crystals possessed adjacent re-entry structures between the right- and left-handed stems along the (100) and (010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 67 publications
15
112
0
Order By: Relevance
“…Solid-state NMR (SS-NMR) is a sophisticated technique for the structural and dynamic analysis of inorganic materials and organic molecules [15][16][17][18][19][20][21]. Among the various magnetic interactions, dipolar interactions, which are inversely proportional to the third power of the internuclear distance, have been successfully used to determine the local conformation and packing of polymers [15] and peptides [16,17], intermolecular interactions of self-assembly systems [18] and 3D structure of peptides [19] and proteins [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state NMR (SS-NMR) is a sophisticated technique for the structural and dynamic analysis of inorganic materials and organic molecules [15][16][17][18][19][20][21]. Among the various magnetic interactions, dipolar interactions, which are inversely proportional to the third power of the internuclear distance, have been successfully used to determine the local conformation and packing of polymers [15] and peptides [16,17], intermolecular interactions of self-assembly systems [18] and 3D structure of peptides [19] and proteins [20].…”
mentioning
confidence: 99%
“…Among the various magnetic interactions, dipolar interactions, which are inversely proportional to the third power of the internuclear distance, have been successfully used to determine the local conformation and packing of polymers [15] and peptides [16,17], intermolecular interactions of self-assembly systems [18] and 3D structure of peptides [19] and proteins [20]. Recently, we proposed a strategy to investigate detailed CF structures in which the adjacent re-entry sites, successive adjacent re-entry number <n>, and adjacent re-entry fraction <F> are obtained from the analysis of 13 C- 13 C double-quantum (DQ) buildup curves [21]. Such data is sensitive to the spatial arrangement of 13 C labels, and detailed information on the chain folding is obtained by comparison with data simulated on the basis of different models.…”
mentioning
confidence: 99%
“…With folded‐chain cluster as research objects, let us see their stress conditions. Recently, Miyoshi et al found with 13 C‐ 13 C double‐quantum NMR that a chain existed mainly in the form of folded‐chain cluster in PB‐1 crystals . These clusters included two or three stems, which can be regarded as a crystal embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Miyoshi et al found with 13 C-13 C doublequantum NMR that a chain existed mainly in the form of foldedchain cluster in PB-1 crystals. [62][63][64] These clusters included two or three stems, [64] which can be regarded as a crystal embryos. These crystal embryos may be in different states due to different stress conditions, as seen in Figure 14.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they acquired the morphology and the corresponding diffraction pattern of the single crystals under a transmission electron microscope, both of which confirmed the formation of a folded chain structure. Subsequent computer simulation [20][21][22][23][24][25][26] and experiments [27][28][29][30] also revealed that a single polymer chain would spontaneously crystallize in a folded manner within an appropriate temperature range.…”
Section: Solution-grown Single Crystalsmentioning
confidence: 97%